Pengaruh kejelasan sasaran anggaran, desentralisasi dan akuntabilitas publik terhadap kinerja manajerial Satuan Kerja Perangkat Daerah (Studi empiris pada SKPD Pemerintah Kota Pekanbaru) - Wahyuni, Rizka; Rasuli, Muhammad; Diyanto, Volta (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
The purpose of this research is to know whether the influence of budget goal clarity, decentralization and public accountability of SKPD managerial performance. The technical data collection of this survey is the questionnaire directly sent to the SKPD city government of pekanbaru. Total of respondents used in this research is 94 respondents (78,33%). The method of analysis used is the multiple linear regression using SPSS version 21. The result of this research showed that simultaneous regression test (F-test) is budget goal clarity, decentralization and public accountability influence to the managerial performance on SKPD. The result of partial regression test (T-test) showed that decentralization have significant influence to managerial performance of SKPD, but budget goal clarity and public accountability is contrary. The coefficient determination (R2) effect by all independent variables are 24,8% while the remaining 75,2% influenced by other variables were not examined in this study.Keywords: Managerial Perfomance, Budget Goal Clarity, Decentralization and Public Accountability